Economic Policies for a New South Africa - Lachman, Desmond; Bercuson, Kenneth (Washington, D.C. : International Monetary Fund, 1992)
Against a backdrop of the dismantling of apartheid and the current government's commitment to negotiating a new constitution based on universal suffrage and protected human rights, discussions are under way on the appropriate economic policies to be pursued in the new political climate. This paper focuses on the redistributive and growth policies needed in the new South Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet